The Ethical Line Connecting Hieroglyphics to Hyperlinks - Grinstein, Gidi (International Journal of Civilizations Studies & Tolerance Sciences, 2024)
In this day and age, societies are disrupted and their order is unraveled at an unprecedented pace due to accelerating technological and societal change. Millions of people and countless communities are faced with hitherto unknown and complex conditions, on a breathtaking scale. This reality requires creating more societal knowledge, faster than ever before. Such knowledge-creation will be significantly enhanced if it relies on civilizational dialogue and shared wisdom across religious, national, ethnic, and political lines. This article points to a surprisingly inspiring story in contending with such challenges – which is the biblical story about the gladiatorial clash in ancient Egypt between Pharaoh, the demi-god representing polytheism and ancient Egypt’s caste-based society; and Moses, the teacher-leader of the enslaved Hebrews, representing monotheism and the ethos of natural universal human rights. That clash was a turning point in human history because the victory of monotheism over idolatry allowed for the inception and evolution of constitutional and legal systems that were based on the notion of fundamental equality among all humans. Moses is one of the most influential historical figures in human history, whose legacy continues to inspire billions of Muslims, Christians, Jews, and others. The issues that underlie his bout with Pharaoh – justice vs. idolatry, equality vs. privilege, and freedom vs. bondage – continue to challenge and shape our modern societies. Therefore, Moses’s outlook remains the cornerstone of any modern worldview that embraces diversity and advances tolerance.
Keywords: Monotheism; polytheism; Abrahamic religions; Societal disruption; tolerance; justice; idolatry; law; Abraham